The Influence of Working Capital Management, Financial Charges, and Macroeconomics On Profitability in The Building Construction Sub-Sector - Andina Nuraini Ginoga; Nimmi Zulbainarni; Trias Andati (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Efficient working capital management is critical for building construction companies. Inadequate management can lead to operational inefficiencies, elevated financial charges, and reduced profitability. The stability of the national economy can also influence corporate performance. Purpose: This study aims to analyze the impact of working capital management, financial charges, and macroeconomic factors on the profitability of building construction sub-sectors. Design/methodology/approach: This study utilizes quarterly financial report data from ten construction companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2023. Macroeconomic data is obtained from the Badan Pusat Statistik and Bank Indonesia. The data is analyzed using descriptive statistics, comparative testing, and panel data regression. Findings/Results: Descriptive statistics indicate a fluctuating trend during the observation period, with days of sales outstanding dominating cash conversion cycle. Comparative tests reveal significant differences in working capital management, interest coverage ratio, and profitability before and during COVID-19. The panel data regression results indicate that days of inventory outstanding, days of payable outstanding, debt to equity ratio, working capital interest rates, construction GDP growth, and sales growth all have significant effects on profitability. Originality/value (State of the art): Thus, it can be concluded that the manager of building construction companies must give significant attention to the management of accounts payable and liabilities to enhance profitability. Keywords: building construction, financial charges, macroeconomics, profitability, working capital management